2012
DOI: 10.1017/s1049023x12001100
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Needs Assessment After the Gulf Coast Oil Spill—Alabama and Mississippi, 2010

Abstract: The proportion of respondents reporting negative mental health parameters in the affected Alabama and Mississippi coastal communities is higher than the proportion reported in the 2008 and 2009 BRFSS state reports, suggesting that the public health response to the Deepwater Horizon oil spill should focus on mental health services in these communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…Increased rates of depression after disasters have been well-documented (Arata et al 2000; Buttke et al 2012; Carrasco et al 2007; Cerdá et al 2013; Galea et al 2002; Lyons et al 1999; McLeish and Del Ben 2008), and the results of the present study confirm these findings. Using the same metric, though not directly comparable, only ~20% of individuals in the general population would be expected to exhibit depressive symptoms (Radloff 1977).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Increased rates of depression after disasters have been well-documented (Arata et al 2000; Buttke et al 2012; Carrasco et al 2007; Cerdá et al 2013; Galea et al 2002; Lyons et al 1999; McLeish and Del Ben 2008), and the results of the present study confirm these findings. Using the same metric, though not directly comparable, only ~20% of individuals in the general population would be expected to exhibit depressive symptoms (Radloff 1977).…”
Section: Discussionsupporting
confidence: 89%
“…Early observations of psychological and economic harm immediately following the DHOS have also been reported (Buttke et al 2012; Osofsky et al 2011), with striking similarities in resultant health effects noted between the DHOS and previous spills (Gill et al 2012). A 2011 survey conducted by the Gulf State Population Survey (GSPS) revealed that direct exposure to the oil spill itself was the most important determinant of mental health (Fan et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly an indirect association was revealed, where individuals that applied for financial assistance following the oil spill reported fewer symptoms of anxiety. This finding may support reports that the application process was overly complicated and was unattainable for the business practices of self-employed individuals in the fishing industries [23,24]. Contrary to the Exxon Valdez findings of Picou, Marshall and Gill [35], the low association between anxiety and litigation was no longer significant when accounting for the other variables.…”
Section: Discussionsupporting
confidence: 68%
“…Given that the location of the oil spill affected individuals and communities with prior devastation from Hurricane Katrina, results also revealed that losses from Hurricane Katrina were highly associated with negative mental health outcomes, however the oil spill distress had unique variance in the analyses supporting that the DWH Gulf Oil Spill represents a complex recovery [19]. Additional studies conducted across the Gulf States have concurred with these findings and support the need for continued mental health treatment of children and adults, due to increased mental health concerns and symptoms [20][21][22][23][24]. In contrast, findings from a federal studies found a lack of increase in mental health symptoms following the oil spill; however, the authors note that a limitation with their study is that the broad population based surveillance methods may underestimate prevalence due to individuals directly affected living in smaller sub-communities [25].…”
Section: Deepwater Horizon Gulf Oil Spillmentioning
confidence: 66%
“…13 Changes in the tourism and associated real estate, restaurant, and entertainment industries of the Gulf Coast following the oil spill affected income levels for many employed in these areas, and raised financial concerns for those whose income may be indirectly influenced by the overall community business climate. 6 These effects may have been further exacerbated by the global economic recession. A situation therefore existed that may have triggered financial concerns in a broader range of individuals than those directly economically affected by the oil spill, and may have further increased mental health needs in the community.…”
Section: Discussionmentioning
confidence: 99%